Attention-based lane change prediction - Scheel, Oliver; Nagaraja, Naveen Shankar; Schwarz, Loren; Navab, Nassir; Tombari, Federico (Proceedings - IEEE International Conference on Robotics and Automation, 2019)
Lane change prediction of surrounding vehicles is a key building block of path planning. The focus has been on increasing the accuracy of prediction by posing it purely as a function estimation problem at the cost of model understandability. However, the efficacy of any lane change prediction model can be improved when both corner and failure cases are humanly understandable. We propose an attention-based recurrent model to tackle both understandability and prediction quality. We also propose metrics which reflect the discomfort felt by the driver. We show encouraging results on a publicly available dataset and proprietary fleet data.
CRIS-Team Scopus Importer:2023-03-08